IDENTIFICATION OF SYNGONIUM PODOPHYLLUM SCHOTT PIGMENTÃâÃâS PERFORMANCE AS NATURAL PHOTOSENSITIZER IN DYE SENSITIZED SOLAR CELLS - ODE NIRWANA SARI HALIDUN , WA
Photosynthetic pigments have good potential in electron transfer processes as well as having a light absorption ability on the visible wavelength spectrum of light that is greater than that of organometallic dye. So this photosynthetic pigment can be used as one of nature's alternative eco-friendly photosensitizer. Syngonium podophyllum Schott is a type of vines, easy available, and has a lot of chlorophyll. So it can be used as a natural source of photosensitizer. This study aims to identify the performance of pigment leaves Syngonium podophyllum Schott as a natural photosensitizer. The fractionation is conducted to separate the photosynthetic pigment of Syngonium podophyllum Schott. Four type of fraction were obtained then called fraction 1, fraction 2, fraction 3 and fraction 4. The Uv-vis and FTIR spectroscopy was performed to identify the pigment of Syngonium podophyllum Schott leaves, so that obtained pigment of carotenoid, pheophytin, chlorophyll a and chlorophyll b. The concentrations of each pigment were obtained from the Uv-vis spectroscopy analysis of 49.054 mg / L, 1.451 mg / L, 9.14 mg / L, 11.79 mg / L and 12.178 mg / L for unfraction, fraction 1, fraction 2, fraction 3 and fraction 4 respectively. Analysis of HOMO-LUMO and gap energy have obtained by combination technique of uv-vis and cyclic voltametri. The results showed that the unfractionated dye showed LUMO energy level nearing the TiO2 conduction band of 3.6 eV and gap energy of 1,8128 eV. Impedance spectroscopy showed the smallest electron transport resistance of 6 ? with a very slow recombination time of 11.57 × 10-4 s and the greatest chemical and electronactivity capacities of 7.54 × 10-6 F and 3.11 × 10-4cm-1?-1. Based on this, the best performance of DSSC is shown by the non-fractionated dye of 1.06%, compared with the dye performance of fraction 1, fraction 2, fraction 3 and fraction 4 with eficiency of 0.074%, 0.110%, 0.302%, and 0.168%.